Magnetic Reconnection, Turbulence, and Particle Acceleration: Observations in the Earth's Magnetotail. Issue 8 (19th April 2018) - Ergun, R. E.; Goodrich, K. A.; Wilder, F. D.; Ahmadi, N.; Holmes, J. C.; Eriksson, S.; Stawarz, J. E.; Nakamura, R.; Genestreti, K. J.; Hesse, M.; Burch, J. L.; Torbert, R. B.; et al.
Abstract: We report observations of turbulent dissipation and particle acceleration from large‐amplitude electric fields ( E ) associated with strong magnetic field ( B ) fluctuations in the Earth's plasma sheet. The turbulence occurs in a region of depleted density with anti‐earthward flows followed by earthward flows suggesting ongoing magnetic reconnection. In the turbulent region, ions and electrons have a significant increase in energy, occasionally >100 keV, and strong variation. There are numerous occurrences of | E | >100 mV/m including occurrences of large potentials (>1 kV) parallel to B and occurrences with extraordinarily large J  ·  E ( J is current density). In this event, we find that the perpendicular contribution of J  ·  E with frequencies near or below the ion cyclotron frequency ( f ci ) provide the majority net positive J  ·  E . Large‐amplitude parallel E events with frequencies above f ci to several times the lower hybrid frequency provide significant dissipation and can result in energetic electron acceleration. Plain Language Summary: The Magnetospheric Multiscale mission is able to examine dissipation associated with magnetic reconnection with unprecedented accuracy and frequency response. The observations show that roughly 80% of the dissipation is from the perpendicular currents and electric fields. However, large‐amplitude parallel electric fields appear to play a strong role in turbulent dissipation into electrons and in electron acceleration. Key Points: MMS observations reveal characteristics of turbulent dissipation and particle acceleration associated with magnetic reconnection Perpendicular electric fields and large‐amplitude parallel electric fields structures have dominant roles in turbulent dissipation Turbulent electric fields in a magnetic structure is shown to play a key role in accelerating electrons to greater than 100 keV energies